2021
DOI: 10.26603/001c.18823
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Neuromotor Retraining to Augment Manual Therapy and Vestibular Rehabilitation in a Patient with Post-Concussion Syndrome: A Case Report

Abstract: Background and Purpose Less than half of patients discharged from the emergency department post-concussion receive patient education or follow-up care, and 10-20% of individuals will develop symptoms that last longer than six months. Current research on interventions for post-concussion syndrome (PCS) shows inconsistent results, and recommendations for effective physical therapy treatment for patients with chronic PCS are lacking. The purpose of this case report is to highlight a successful, multi-system appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Similarly, self‐reported discomfort when exposed to a computer screen decreased when using a non‐liquid crystal display (non‐LCD) screen (Mansur et al, 2018) that refreshed at a lower rate than a standard LCD screen. Lastly, Gunter et al (2018) and Teare‐Ketter et al (2021) described cases with light hypersensitivity after a mTBI. The cases were both symptom free after several weeks of physical therapy (no specific treatment for the hypersensitivity symptoms was mentioned).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, self‐reported discomfort when exposed to a computer screen decreased when using a non‐liquid crystal display (non‐LCD) screen (Mansur et al, 2018) that refreshed at a lower rate than a standard LCD screen. Lastly, Gunter et al (2018) and Teare‐Ketter et al (2021) described cases with light hypersensitivity after a mTBI. The cases were both symptom free after several weeks of physical therapy (no specific treatment for the hypersensitivity symptoms was mentioned).…”
Section: Resultsmentioning
confidence: 99%
“… 19 Case studies have shown VOR disruption in those with PPCS. 20 21 Common complaints of vestibular dysfunction include dizziness, vertigo, nausea, fogginess, unsteady gait and postural instability. 15 22 The most common oculomotor disorders following a concussion are convergence insufficiency (affecting the ability of eyes to work together to clearly see nearby objects) and accommodative insufficiency (difficulty when focussing on a nearby object).…”
Section: Introductionmentioning
confidence: 99%
“…The vestibulo-ocular reflex (VOR) is a complex reflex that serves to maintain balance and spatial orientation by stabilising the gaze during head movement 19. Case studies have shown VOR disruption in those with PPCS 20 21. Common complaints of vestibular dysfunction include dizziness, vertigo, nausea, fogginess, unsteady gait and postural instability 15 22.…”
Section: Introductionmentioning
confidence: 99%
“…The vestibulo-ocular re ex (VOR) is a complex re ex that involves the vestibular and visual systems which functions to maintain balance and spatial orientation by stabilizing gaze during head movement (24). Case studies have shown VOR disruption in those with PCS (25,26). Common complaints of vestibular dysfunction include dizziness, vertigo, nausea, fogginess, unsteady gait, and postural instability (20,27).…”
Section: Introductionmentioning
confidence: 99%